Semantic architecture for the analysis of the academic and occupational profiles based on competencies - Aguilar Castro, J. (2016)
This research shows a semantic architecture for the extraction, comparison and feedback of professional and educational competencies. The main product is a scheme that facilitates the detection of competencies based on the skills and knowledge. The scheme carries out tasks of natural language processing and of similarity calculation, among others, in order to determine the differences among the professional and educational competencies. © 2015 Alexandra González Eras and Jose Aguilar